(untitled) (Polish Yearbook of International Law, 2023)
The anniversaries of the 1970 Warsaw and the 1990 2+4 Treaties give occasion to revisit the matter of minority protection in German-Polish relations. The interwar system established a problematic unevenness that tainted its acceptance, particularly from the Polish perspective. After 1990 the minority issues achieved an increased, albeit moderate, relevance in German-Polish relations. To some extent the 1991 Polish-German Treaty on Good Neighbourly Relations and Friendly Co-operation retains the unevenness of the inter-war period, as Art. 20(1) recognizes a German minority in Poland, but refuses to acknowledge a Polish minority in Germany. However, currently the thorniest issues concern various situations related to the “Silesians” in Poland, which the Polish government does not recognize as a protected minority under the European Council Framework Convention for the Protection of National Minorities.